Coo - Noel, Kaela (Greenwillow Books, an imprint of HarperCollins Publishers, 2021)
"Coo, a ten-year-old girl raised by a flock of pigeons, delights in finally making human contact, but quickly learns that our world is more cruel and complicated than she could have guessed"--Provided by publisher.